Decoded Calreticulin-Deficient Embryonic Stem Cell Transcriptome Resolves Latent Cardiophenotype - Faustino, Randolph S. (2010)
Genomic perturbations that challenge normal signaling at the pluripotent stage may trigger unforeseen ontogenic aberrancies. Anticipatory systems biology identification of transcriptome landscapes that underlie latent phenotypes would offer molecular diagnosis before the onset of symptoms. The purpose of this study was to assess the impact of calreticulin-deficient embryonic stem cell transcriptomes on molecular functions and physiological systems. Bioinformatic surveillance of calreticulin-null stem cells, a monogenic insult model, diagnosed a disruption in transcriptome dynamics, which re-prioritized essential cellular functions. Calreticulin-calibrated signaling axes were uncovered, and network-wide cartography of undifferentiated stem cell transcripts suggested cardiac manifestations. Calreticulin-deficient stem cell-derived cardiac cells verified disorganized sarcomerogenesis, mitochondrial paucity, and cytoarchitectural aberrations to validate calreticulin-dependent network forecasts. Furthermore, magnetic resonance imaging and histopathology detected a ventricular septal defect, revealing organogenic manifestation of calreticulin deletion. Thus, bioinformatic deciphering of a primordial calreticulin-deficient transcriptome decoded at the pluripotent stem cell stage a reconfigured multifunctional molecular registry to anticipate predifferentiation susceptibility toward abnormal cardiophenotype.